The positive side of bank wealth management products: Evidence from bank lending rate - Wang, Zhanhao; Zhao, Hong; Li, Lingxiang (Journal of Financial Stability, 2022)
The systemic risk and negative social impacts from bank-issued wealth management products (WMPs) are well studied by scholars and practitioners in China. Using hand-collected bank data, we find that WMPs help reduce banks’ cost of funds, which is then passed on to their borrowers as lower borrowing cost. This finding shows an upside of this controversial but increasingly popular bank product. We propose four mechanisms through which WMPs can lower banks’ cost of funds: structural change in deposits, cross-subsidization, liquidity effect, and related-party transactions. We find supporting evidence for those mechanisms, and their effects vary across state-owned, joint-stock, and city commercial banks. Those variations are consistent with the unique characteristics of each bank group. We further explore the competition for capital between state-owned and non-state-owned banks. The results suggest that state-owned banks offer significantly higher interest rates for deposits as non-state-owned banks expand in the same region. WMP issuance is likely a differentiation strategy in response to the competition for deposits.